Implementasi visi misi bisnis dalam organisasi profit dan non profit - Hasanah, Binti Roisul (Maliki Interdisciplinary Journal, 2024)
The business vision and mission are very good at being operationalized as the key to an organization’s success. The vision presents a picture of the future that the organization or company will achieve, while the mission determines the fundamental goals and primary values ​​that serve as guidelines for achieving the previously determined vision. Using the correct vision and mission will really help the organization focus more on long-term success and produce higher-quality profits and services. Thus, it is not uncommon for the right institution/company to implement a vision and mission that is directed, clear, and on target to excel in their business. By understanding and implementing a superior vision and mission, organizations can create a complete foundation for better long-term sustainability and growth.